High-quality physiology of Alcanivorax borkumensis SK2 producing glycolipids enables efficient stirred-tank bioreactor cultivation - Karmainski, Tobias; Dielentheis-Frenken, Marie R. E.; Lipa, Marie K.; Phan, An N. T.; Blank, Lars M.; Tiso, Till (Frontiers in Bioengineering and Biotechnology, 2023)
Glycine-glucolipid, a glycolipid, is natively synthesized by the marine bacterium Alcanivorax borkumensis SK2. A. borkumensis is a Gram-negative, non-motile, aerobic, halophilic, rod-shaped γproteobacterium, classified as an obligate hydrocarbonoclastic bacterium. Naturally, this bacterium exists in low cell numbers in unpolluted marine environments, but during oil spills, the cell number significantly increases and can account for up to 90% of the microbial community responsible for oil degradation. This growth surge is attributed to two remarkable abilities: hydrocarbon degradation and membrane-associated biosurfactant production. This study aimed to characterize and enhance the growth and biosurfactant production of A. borkumensis, which initially exhibited poor growth in the previously published ONR7a, a defined salt medium. Various online analytic tools for monitoring growth were employed to optimize the published medium, leading to improved growth rates and elongated growth on pyruvate as a carbon source. The modified medium was supplemented with different carbon sources to stimulate glycine-glucolipid production. Pyruvate, acetate, and various hydrophobic carbon sources were utilized for glycolipid production. Growth was monitored via online determined oxygen transfer rate in shake flasks, while a recently published hyphenated HPLC-MS method was used for glycine-glucolipid analytics. To transfer into 3 L stirred-tank bioreactor, aerated batch fermentations were conducted using n-tetradecane and acetate as carbon sources. The challenge of foam formation was overcome using bubble-free membrane aeration with acetate as the carbon source. In conclusion, the growth kinetics of A. borkumensis and glycine-glucolipid production were significantly improved, while reaching product titers relevant for applications remains a challenge.